PROGRESS IN SURGICAL TREATMENT OF CHRONIC LOWER LIMB ISCHEMIA - O. A. Alukhanyan; X. G. Маrtyrosya; I. V. Poluektova; V. A. Avakimyan (Кубанский научный медицинский вестник, 2018)
Aim. The study was conducted to expand the variety of ways for surgical treatment of chronic ischemia of lower limbs complicated by the involvement of the femoropopliteal and pedidial arterial segment. Materials and methods. The experience of surgical interventions in 43 male patients aged 52-75 suffering from chronic ischemia of lower limbs complicated by the atherosclerotic involvement of the femoropopliteal and pedidial segment has been summarized. According to the classification by A.V. Pokrovskiy, ischemia of the 3rd stage has been determined in 24 patients (55,8%), while ischemia of the 4th stage complicated by necrosis of the toes (critical ischemia) has been determined in other 19 patients (44,2%). All examined patients have undergone the reconstructive interventions using the prepared lateral subcutaneous vein of the upper extremity as a shunt.Results. During the first day after the operation, the regression of pain syndrome as well as the warming of the lower extremity was indicated in 93% of patients. In 8-12 days after the reconstructive operation, the patients have undergone the 15 necrectomy or toe amputation. In the nearest postoperative period (less than 6 months) no thrombotic complications in the reconstructed segment have been determined. Within the observation period from 6 months to 5 years the bypass patency has been preserved in 71% of patients; ischemia of the 2nd B type has been revealed in all patients with the preserved bypass patency by the clinical examination.Conclusion. Despite the “forced” character of usage of the prepared V. cephalica due to the absence of “traditional” venous shunts as well as the labor intensity of the method, it allows to expand the variety of ways for surgical treatment of patients suffering from chronic ischemia of lower limbs of the 3rd-4th stages complicated by occlusive involvements of the femoropopliteal and pedidial segment.